2013
DOI: 10.1371/journal.pone.0067697
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically Homogeneous Red Blood Cells Present a Heterogeneous Response to Hormonal Stimulation

Abstract: Red blood cells (RBCs) are among the most intensively studied cells in natural history, elucidating numerous principles and ground-breaking knowledge in cell biology. Morphologically, RBCs are largely homogeneous, and most of the functional studies have been performed on large populations of cells, masking putative cellular variations. We studied human and mouse RBCs by live-cell video imaging, which allowed single cells to be followed over time. In particular we analysed functional responses to hormonal stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 66 publications
2
53
1
Order By: Relevance
“…The results are shown in Figure 2. The heterogeneity of the data is not caused by inter-individual differences but by a heterogeneous response of the cells similar as reported before for the stimulation with Lysophospatidic acid [21]. In murine RBCs, Epo as well as PGE 2 induced a clear increase in the intracellular Ca…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results are shown in Figure 2. The heterogeneity of the data is not caused by inter-individual differences but by a heterogeneous response of the cells similar as reported before for the stimulation with Lysophospatidic acid [21]. In murine RBCs, Epo as well as PGE 2 induced a clear increase in the intracellular Ca…”
Section: Resultssupporting
confidence: 78%
“…Wild-type mice were C57Bl6/N, the same as the background of the dKO mice. For enriching reticulocytes (RNA) in the blood samples, mice were treated for an induction of a reticulocytosis as described before [21]. These experiments were conducted in accordance with the recommendations of the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of RBC activation using LPA from different companies In our experiments described in previous papers [3,15,16,21] we realised that RBC stimulation with LPA from different batches obtained from Sigma-Aldrich led to significant different results of the intracellular Ca 2+ content as well as PS exposure. To investigate this phenomenon in more detail we performed experiments with LPA from 4 different batches, 2 from Sigma-Aldrich, one from Cayman Chemical Company, and one from Santa Cruz Biotechnology Inc. All 4 LPA probes were freshly ordered, re-frozen only once and were applied to the same blood on the same day and using the same HPS.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, no direct evidence has been reported that increased intracellular Ca 2+ levels are vital to eryptosis. However, a study has reported the heterogeneity between the elevation of intracellular Ca 2+ concentrations and increased eryptosis [41] where RBCs eryptosis occurs without the involvement of Ca 2+ [20]. In this study, we observed that Ca 2+ influx occurred within 6 h after Cr 6+ exposure.…”
Section: Discussionmentioning
confidence: 44%